Trending on the Edge: Social Media’s Impact on Gen Z’s Dark Thana Tourism Choices. - Budnikevich, Iryna; Krupenna, Inha; Буднікевич, Ірина Михайлівна; Крупенна, Інга Анатолівна (Springer Nature Switzerland AG, 2024)
Dark Tourism, characterized by visits to sites associated with death, tragedy, and suffering, has seen a significant surge in popularity, particularly among Generation Z (Gen Z). This study investigates the crucial role of social media in shaping the choices and perceptions of Gen Z when it comes to Dark Tourism destinations. In the digital age, where information spreads quickly, social media platforms have become instrumental in driving the growth of Dark Tourism. With a sample of 156 respondents, this research examines the interactions between demographic factors (gender, age, education) and specific variables (Content Type, Followed Accounts/Profiles, Engagement Metrics, Peer Influence, Hashtags and Trends) in influencing Dark Tourism choices. Using a mixed-methods approach that combines surveys and qualitative content analysis, this study offers insights into the multifaceted world of Dark Tourism and how it intersects with social media, demographics, and the choices of modern travellers.
Keywords: Social Media’s; Gen Z’s; Dark Thana; Tourism Choices; marketing trends; tourism marketing